2016
DOI: 10.1080/14615517.2016.1177934
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment in Hong Kong: a comparison study and lessons learnt

Abstract: a department of civil and environmental engineering, University of Illinois at Urbana-champaign, Urbana, Il, Usa; b department of Building and real estate, the Hong Kong polytechnic University, Hong Kong, china; c school of construction management and real estate, the chongqing University, chongqing, china ABSTRACT Although many studies in developed countries on the practice of EIA have been conducted, there is a lack of similar attention in Hong Kong. This gap in knowledge is addressed in this study which sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The focus of the EC conditions appears to be more on compliance with the regulatory requirements than on meeting the objectives of the EIA [13,27] . On the lines of the environmental permits granted in Hong Kong [20] , the EC conditions should effectively bind project proponents to implement the well prepared and documented mitigation measures to prevent environmental issues. In addition to highlights of the project and location-related details for land, water, solid waste, and wastewater, the EC letters for the projects could be consistently enriched with the highlights of pre-project land use/land cover, designated ESA, flora and fauna-related concern, project affected population, realistic employment potential, the concern raised in the public consultation process, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of the EC conditions appears to be more on compliance with the regulatory requirements than on meeting the objectives of the EIA [13,27] . On the lines of the environmental permits granted in Hong Kong [20] , the EC conditions should effectively bind project proponents to implement the well prepared and documented mitigation measures to prevent environmental issues. In addition to highlights of the project and location-related details for land, water, solid waste, and wastewater, the EC letters for the projects could be consistently enriched with the highlights of pre-project land use/land cover, designated ESA, flora and fauna-related concern, project affected population, realistic employment potential, the concern raised in the public consultation process, etc.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general understanding in Hong Kong that the permit conditions effectively bind project proponents to implement the agreed mitigation measures to prevent environmental issues [20] . The conditions prescribed to project proponents in 801 documents to perform ex-ante and ex-post monitoring of potential impacts described in the EIA reports were characterized [21] and it was concluded that post-project monitoring remained a challenge.…”
Section: Introductionmentioning
confidence: 99%